A Series of Discrete Dichloride Dihydrates: Characterisation and Symmetry Effects - Senthooran, Rathiga; Curnow, Owen J.; Brenner, Thomas; Weiss, Robert; Ferreras, Manuel; Crittenden, Deborah L. (ChemPlusChem, 2020)
A series of three discrete dichloride dihydrates [Cl2(H2O)2]2− have been isolated with different triaminocyclopropenium (TAC) cations and with different crystallographic symmetries. The cluster exhibits D2h symmetry with the tris(dimethylamino)cyclopropenium cation [C3(NMe2)3]+, C2h symmetry with the fluorinated cation [C3(N(CH2CF3)2)(NBu2)2]+ (containing two 2,2,2-trifluoroethyl substituents) and C2v symmetry with the more fluorinated [C3(N(CH2CF3)2)2(NBu2)]+ cation. The effect of symmetry on the infrared spectra of the dichloride ion-pair clusters, as well as deuterated analogues, has been investigated. The D2h- and C2h-symmetric clusters each exhibit two stretching bands in the infrared at 3427 and 3368 cm−1 for D2h symmetry and 3444 and 3392 cm−1 for C2h symmetry, whereas the C2v-symmetric cluster exhibits three bands at 3475, 3426 and 3373 cm−1. Computational studies were carried out on a [Cl2(H2O)2]2− cluster with C2v symmetry to aid the infrared band assignments.
CRIS-Team Scopus Importer:2020-09-18
Keywords: cyclopropenium cations; dichlorides; hydrates; ion-pair clusters; symmetry